2007
DOI: 10.3892/or.18.2.433
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of a combination of trastuzumab (Herceptin) and oral fluoropyrimidine S-1 on human epidermal growth factor receptor 2-overexpressing pancreatic cancer

Abstract: The cytotoxic effect of trastuzumab in combination with oral fluoropyrimidine S-1 on human epidermal growth factor receptor 2 (HER2)-overexpressing human pancreatic cancer cell line TRG in vitro and in vivo was investigated. HER2 expression in TRG was analyzed by RT-PCR and flow cytometry. For in vitro experiments, 5-fluorouracil (5-FU) was used instead of S-1. In vivo studies were conducted with TRG xenografts in athymic mice. Trastuzumab (10 mg/kg) was administered intraperitoneally once a week for 4 weeks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…On the basis of these mixed Wndings, there is some evidence for ErbB-2 as a prognostic indicator, although future studies with larger sample numbers are required to conWrm this. Furthermore, drugs blocking ErbB-2 like herceptin, used successfully in breast cancer clinically (Lin and Rugo 2007) and other cancers in vitro (Saeki et al 2007), may be beneWcial if patients with osteosarcoma were found to over express ErbB-2.…”
Section: Erbb-2mentioning
confidence: 98%
“…On the basis of these mixed Wndings, there is some evidence for ErbB-2 as a prognostic indicator, although future studies with larger sample numbers are required to conWrm this. Furthermore, drugs blocking ErbB-2 like herceptin, used successfully in breast cancer clinically (Lin and Rugo 2007) and other cancers in vitro (Saeki et al 2007), may be beneWcial if patients with osteosarcoma were found to over express ErbB-2.…”
Section: Erbb-2mentioning
confidence: 98%
“…Significant synergism was found as well with transuzumab and the fluopyrimidines, on pancreatic cancer cell lines, both in vivo and in vitro (5-fluorouracil was used in vitro and S-1, an oral compound, in vivo) [108]. The examined pancreatic cancer cell lines TRG were overexpressing the HER2/neu receptor and treatment with the antibody and the cytotoxic drug significantly inhibited the tumor volume and growth [108].…”
Section: Trastuzumabmentioning
confidence: 97%
“…The examined pancreatic cancer cell lines TRG were overexpressing the HER2/neu receptor and treatment with the antibody and the cytotoxic drug significantly inhibited the tumor volume and growth [108].…”
Section: Trastuzumabmentioning
confidence: 99%
“…Additive effects were observed when trastuzumab was combined with fluoropyrimidine S-1 both in vitro and in vivo (fluoropyrimidine S-1 is an oral preparation of 5-fluorouracil [5-FU] that consists of tegafur [a prodrug of 5-FU], 5-chloro-2,4-dihydoxypyridine and potassium oxonate, where the latter two can inhibit degradation of 5-FU and reduce gastrointestinal toxicity). In addition to the inhibition of the HER2 signal transduction pathway, antibody-dependent cellular cytotoxicity (ADCC) induced by trastuzumab contributed to cell growth inhibition [30]. Many effector cells in the immune system express IgG Fc receptors, which may activate the effector cells upon binding with specific antibodies.…”
Section: Target Molecules On the Cell Surfacementioning
confidence: 99%